Po zagładzie Rzeczypospolitej - Maciąg, Kazimierz (Tematy i Konteksty, 2016)
In his review Kazimierz Maciąg analyses a three-volume study by Piotr Żbikowski on the Polish language press “for the Poles” published in the three partitions in the period between the loss of independence and the entry of Napoleon’s army on Polish soil (Pod rządami Franciszka Habsburga – cesarza Austrii; W monarchii pruskiej; W imperium carów). The books by this eminent scholar of literature from the end of the 18th to the first decades of the 19th c. depict an extremely interesting panorama of the life of Polish people in the first decade after the partitions. We shall find in them not only an outline of the political situation, but also remarks on economic life, education and cultural changes on Polish soil. The documentary value of Piotr Żbikowski’s study is no less important as we shall find numerous examples illustrating the life of the three monarchs’ new subjects.